ANALISIS PENGARUH TENAGA KERJA, PENDIDIKAN, DAN PENDAPATAN DAERAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR TAHUN 2011-2016 - Juhaina Nur Afifah; Aris Soelistyo (Program Studi Ekonomi Pembangunan, 2019)
Economic growth increased the number of production and income, could be realized without terwujudya development. The increase in economic growth of East Java was seen in Demand Management in form of a PAD, DAU, DAK, and Government spending. Supply Managemnet in form of a Labor and Education. The study uses panel data analysis in the form of Fixed Effect ModelLabor research results do not affect positively not significantly to boost economic growth economic growth of 0.5416% when up by 1%. Education rid by 1% economic growth ride by 190.7056%. Regional income in the form of a PAD went up by 1% economic growth ridee by 18.0789%, DAU went up by 1% economic growth down by 0.3598%, DAK ride by 1% economic growth ride by 2.2397%, government spending ride by 1% economic growth down by 0.0816%The results of regression adjusted R2 value of 0.998315 which is where the independent variables explained about the dependent variable i.e. economic growth of 99.8315% rest of 0.1685% explained by other reasons that are not in the models